Locality in Restaurant Preferences as an Alternative Family Recreative Tourism in Yogyakarta - Stefani Natalia Sabatini; Christmastuti Nur (Program Studi Arsitektur, Fakultas Teknik dan Perencanaan, Universitas Warmadewa, 2023)
The location of culinary services (including restaurants) has now become an alternative for recreational tourism that is popular with the community. On the other hand, cities need regional identity, one of which can be obtained from the sustainability of local values. This paper aims to find the role of locality in restaurant preferences as an alternative to family recreational tourism in the Special Region of Yogyakarta (DIY). Data was obtained through a survey via online questionnaire at the end of 2022 with a total of 115 respondents. As a result, it was found that the number of respondents who explicitly chose a restaurant based on the appearance of the locality aspect was not significant. Even so, the data shows that the restaurants that are favorite by respondents to visit with their families in order to achieve recreational goals tend to have elements of locality, especially in the material and shape aspects. This is thought to be influenced by the character of the majority of families who are invited to enjoy the restaurant by respondents, namely the parents of pre-elderly and elderly respondents who are influenced by nostalgia factors in their preferences as consumers.